(untitled) (Iranian Journal of Kidney Diseases, 2021)
Mycobacterium abscessus complex is one of the most important groups of non-tuberculosis mycobacteria, which can cause infection in several organs of the human body. In this study, we report a rare cause of urinary tract infection which was presented with the chief complaint of hematuria and dysuria. The patient was treated by a clarithromycin based approach and the result of the culture and polymerase chain reaction were negative after 3 months of treatment. Informed consent was taken from the patient for publishing the case.